Human resource management and the institutional perspective - Wood, Geoffrey; Brewster, Chris; Brookes, Michael (New York Routledge, 2014)
"Combining the literature on comparative capitalism with that on comparative HRM, Human Resource Management and the Institutional Perspective explores the overlapping and distinct elements in work and employment relations both within and across country lines. The authors focus on intra-firm relations, internal diversity within varieties of capitalsm, and the uneven and experimental nature of systemic change, all the while employing an impressive level of theoretical rigor and empirical evidence. For those interested in contemporary developments in institutional theory, the relationship between regulation and practice, and in innovation and continuity in HRM, this book is a valuable resource. In a single volume, this text unites soundly based, theoretically strong and empirically new chapters that bring advances in institutional theory to bear on the subject of international and comparative Human Resource Management"--
"Combining the literature on comparative capitalism with that on comparative HRM, Human Resource Management and the Institutional Perspective explores the overlapping and distinct elements in work and employment relations both within and across country lines. The authors focus on intra-firm relations, internal diversity within varieties of capitalism, and the uneven and experimental nature of systemic change, all the while employing an impressive level of theoretical rigor and empirical evidence. For those interested in contemporary developments in institutional theory, the relationship between regulation and practice, and innovation and continuity in HRM, this book is a valuable resource. In a single volume, this text unites soundly based, theoretically strong and empirically new chapters that bring advances in institutional theory to bear on the subject of international and comparative Human Resource Management"--
Keywords: Personnel management; Organizational sociology; BUSINESS & ECONOMICS / Human Resources & Personnel Management; BUSINESS & ECONOMICS / Development / Economic Development; BUSINESS & ECONOMICS / General